Validity and Reliability Study of the Compulsory Citizenship Behaviour Scale in Turkish: A Study Among Nurses - Arzu Kader Harmancı Seren; Nihal Ünaldı Baydın (Association of Nurse Managers, 2017)
INTRODUCTION: This research has been carried out for the purpose of performing validity and reliability of the Compulsory Citizenship Behaviour Scale in Turkish. METHODS: The research is a methodological study. 233 forms which have been filled properly and returned by the sample group that consists of nurses who are working in a public university hospital in Istanbul, were analyzed. Content validity, construct validity, internal consistency, stability and mean scores have been used in the scale evaluation. RESULTS: Content validity index of scale has been found as 0.96. Item mean correlations of the scale were between 0.61-0.77; Cronbach α coefficient of the scale was 0.88, over 0.70 and reliable. Explanatory factor analysis was performed in construct validity. One factor scale structure of the original scale was confirmed. Goodness of fit statistics showed that the goodness of fit indexes of the scale was suitable. The mean total scale score was 3.84+-0.89. DISCUSSION AND CONCLUSION: It has been confirmed that the Compulsory Citizenship Behaviour Scale is reliable and a valid instrument that may be used in studies. The scale is advised to be used in different sample groups in service sector.